Life-Threatening Hypocalcemia following Subtotal Parathyroidectomy in a Patient with Renal Failure and Previous Roux-en-Y Gastric Bypass Surgery - Betsy Palal; Marvin Sinsakul; Sirimon Reutrakul (Case Reports in Endocrinology)
Background. Roux-en-Y gastric bypass (RYGB) can result in calcium and vitamin D deficiency. Parathyroid surgery carries the risk of immediate and long-term hypocalcemia. Methods and Results. We describe a 54-year-old woman with history of end-stage renal disease and gastric bypass surgery who developed calciphylaxis requiring a 3.5-gland parathyroidectomy. Seven weeks later, she presented with weakness, perioral numbness, leg cramps, a positive Chvostek's sign, hypotension, prolonged QT-interval, and serum calcium of 5.4 mg/dL. Oral and intravenous calcium, calcitriol, and high calcium bath hemodialysis were given. She required 18 days of intravenous calcium and an outpatient maintenance regimen of calcitriol 6 mcg/day, calcium carbonate 8 grams/day, calcium citrate 1.2 grams/day, and ergocalciferol 50,000 IU/week. Conclusion. The patient's life-threatening prolonged hypocalcemia and large requirements of calcium and calcitriol were due to a combination of malabsorption, hypoparathyroidism, and renal failure. Special considerations should be given to bariatric surgery patients undergoing neck exploration.